2020
DOI: 10.3389/fonc.2020.00164
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cancer Stem Cells in Radiation Resistance

Abstract: Cancer stem cells (CSC) are a distinct subpopulation within a tumor. They are able to self-renew and differentiate and possess a high capability to repair DNA damage, exhibit low levels of reactive oxygen species (ROS), and proliferate slowly. These features render CSC resistant to various therapies, including radiation therapy (RT). Eradication of all CSC is a requirement for an effective antineoplastic treatment and is therefore of utmost importance for the patient. This makes CSC the prime targets for any t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 211 publications
6
131
0
3
Order By: Relevance
“…OSMR controls BTSC self-renewal and confers resistance to IR. Elevated levels of ROS is shown to sensitize cancer stem cells and tumor response to IR [30][31][32] . Our results demonstrated that inhibition of OSM/OSMR signalling pathway profoundly increased ROS levels, in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…OSMR controls BTSC self-renewal and confers resistance to IR. Elevated levels of ROS is shown to sensitize cancer stem cells and tumor response to IR [30][31][32] . Our results demonstrated that inhibition of OSM/OSMR signalling pathway profoundly increased ROS levels, in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, multicellular spheroids with a diameter larger than approximately 100 ÎŒm contain an internal hypoxic zone caused by the limited distribution of oxygen, nutrients, and metabolites and a necrotic core [ 59 , 60 ]. The hypoxic tumor microenvironment is considered a critical component in determining drug resistance through specific cellular signaling pathways and plays a vital role in regulating the resistance of CSCs to chemotherapy and radiotherapy [ 61 , 62 , 63 , 64 , 65 ]. These findings suggest that our MC-B hydrogel provides a suitable milieu for the growth of these OC cell spheroids, which can be applied for the development of diagnostic and therapeutic strategies for OC.…”
Section: Discussionmentioning
confidence: 99%
“…CSCs are defined as a small proportion of cancer cells with strong self-renewal capacity and multidirectional differentiation potential ( 81 ). Most CSCs are in the G0 phase of cell cycle and are resistant to chemotherapy and radiotherapy, leading to tumor relapse and treatment failure ( 82 , 83 ). Conventional therapies often fail because they do not completely eradicate CSCs, as this subset of cells often evades the treatment via therapy-induced EMT.…”
Section: Micrornas Modulate Drug Resistance-related Mechanisms In Hepmentioning
confidence: 99%